Analisis Deskriptif Pemahaman Bahasa Inggris di Kalangan Pelaku UMKM dalam Industri Keuangan Syariah di Jepara - Fajar Adi Prasetyo; Tata Triswanto; Tiara Noviarini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the level of English proficiency among Micro, Small, and Medium Enterprises (MSMEs) in Kecapi, Jepara, in the context of Islamic finance. English proficiency becomes important because many documents and information related to Islamic financial products are conveyed in English. The research method used is descriptive qualitative with data collection through questionnaires distributed to 50 MSME actors. The research results show that the majority of MSME actors (60%) have a limited understanding of English, while only 15% are able to communicate effectively in the context of international business. Although 70% of respondents recognize the importance of English proficiency to access Sharia financial services, they face obstacles in accessing relevant training. These findings indicate the need for English language training programs that align with the business needs of SMEs, particularly in the sharia finance sector. This research provides practical implications in the form of strategic recommendations for Islamic financial institutions and local governments to support the improvement of English language proficiency among MSME actors, in order to strengthen their competitiveness at the local, national, and international levels.